Pathways to an inner Islam : Massignon, Corbin, Guenon, and Schuon - Laude, Patrick, 1958- (State University of New York Press, 2010)
Pathways to an Inner Islam provides an introduction to the esoteric or spiritual "inner Islam" presented by Western thinkers Louis Massignon, Henry Corbin, Rene Guenon, and Frithjof Schuon. Particularly interested in Sufism--the mystical tradition of Islam--these four twentieth-century authors who wrote in French played an important role in presenting Islamic spirituality to the West and have also had an influence in parts of the Muslim world, such as Turkey, Iran, and Pakistan. Patrick Laude brings them together to argue that an understanding of their inner Islam challenges reductionist views of Islam as an essentially legalistic tradition and highlights its spiritual qualities. The book discusses their thought on the definitions of spiritual Islam and Sufism, the metaphysical and mystical understanding of the Prophet and the Qur'an, the function of femininity in Islamic spirituality, and the inner understanding of jihad. In addition, the writers' Christian backgrounds and.